Magnitude and distribution of cancer in a private teaching hospital, Bahir Dar, Ethiopia - Adugna T Tebabal; Serkadis M Fetene; Solomon K Tessega; Aschalew A Bitew; Oumer A Muhie; Haylemriam A Bayleyegn; Abyot T Teshome; Beselam G Astatkie; Samrawit T Setargew; Ebrahim A Siraj; Ashagrachew T Yayehrad (International Society of Global Health, 2023)
# Background Cancer affects every country in the world irrespective of their developmental status. Since most studies have been performed primarily in public referral hospitals, this study aimed to describe the prevalence and histopathological patterns of cancer in a private setting. Cancer is one of the most common noncommunicable diseases, and regional variations in cancer incidence are responsible for the majority of deaths. The main objective of this study was to determine the magnitude and distribution of cancer among patients at GAMBY Teaching General Hospital. # Methods This retrospective study included a total of 4320 histopathological examination results recorded from January 1, 2016, to December 30, 2020. Descriptive statistics were used to present the results. The SPSS version 26 computer software package was used for data analysis. # Results A total of 4320 examinations revealed that 895 (20.7%) patients had confirmed malignancies. A total of 655 (73.2%) of the cases were females, with a male-to-female ratio of 1:2.73. The mean age of all the confirmed cases was 49.3±14.9 years. The age range was between 2 and 85 years. The mean ages of the females and males were 47.67±13.36 and 53.19±17.93 years, respectively. The most common cancers were cervical cancer (31.9%), breast cancer (12.7%), and skin cancer (11.6%). The top five cancers in the female patients were cervical, breast, nonmelanomatous skin, thyroid, and lymph node malignancies. Among male patients' nonmelanomatous skin cancer, lymph node malignancies, colorectal cancer, bone and soft tissue cancer, and breast cancer constituted the top five cancers. Cancer involving the lung, eye and pancreas is the least common cancer. # Conclusions The results indicate that the pattern of cancer varies significantly from the global pattern of cancer distribution, as do studies in Africa and other regions of the country. The expansion of oncologic services, health education, screening and vaccination services, advancements in diagnostic modalities, and the involvement of the private sector in the management and care of cancer patients are very important health system focuses and forces policy makers to allocate resources accordingly. This study provided good insight into this pattern, but a wider multicenter survey and evaluation of sociodemographic and environmental factors are needed to assess the reasons for the variations.